2017
DOI: 10.1007/s00277-017-3217-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of previously untreated elderly patients with AML: a propensity score-matched comparison of clofarabine vs. FLAG

Abstract: The 5-year overall survival (OS) in patients ≥ 60 years old with acute myeloid leukemia (AML) remains < 10%. Clofarabine-based induction (CLO) provides an alternative to low-intensity therapy (LIT) and palliative care for this population, but supporting data are conflicted. Recently, our institution adopted the FLAG regimen (fludarabine, cytarabine, and granulocyte colony-stimulating factor) based on data reporting similar outcomes to CLO in elderly patients with AML unable to tolerate anthracycline-based indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…Clofarabine is primarily used in older patients and in those with relapsed or refractory disease, and thus prolonged periods of neutropenia are likely the underlying risk factor for IFI. At our institution, use of clofarabine is relatively infrequent given the high toxicity rates of the regimen in less fit and older patients [26–28]. Accordingly, over the study period, use of clofarabine transitioned to being employed primarily in younger patients with very good performance status, which may help explain why clofarabine was not identified as an independent risk factor for IMI in our analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Clofarabine is primarily used in older patients and in those with relapsed or refractory disease, and thus prolonged periods of neutropenia are likely the underlying risk factor for IFI. At our institution, use of clofarabine is relatively infrequent given the high toxicity rates of the regimen in less fit and older patients [26–28]. Accordingly, over the study period, use of clofarabine transitioned to being employed primarily in younger patients with very good performance status, which may help explain why clofarabine was not identified as an independent risk factor for IMI in our analysis.…”
Section: Discussionmentioning
confidence: 97%
“…There were 20 studies addressing this question, reported in 21 publications, 54,62,64,76,80,90,92,101,104,[121][122][123][124][125][126][127][128][129][130][131][132] the majority of which were observational. 54,62,76,80,90,92,101,104,[121][122][123][124][125][126][127][128][129][130][131][132] One study was an RCT 64 in which patients in the standard-of-care arm were preselected by their physicians to receive either intensive (induction) therapy, less-intensive therapy, or best supportive care, vs less-intensive therapy with azacitidine. For this study, for outcomes in which the researchers presented data comparing intensive therapy to azacitidine among patients preselected for intensive therapy, we used this as RCT data.…”
Section: Recommendationmentioning
confidence: 99%
“…Very low-quality evidence suggests that patients who receive intensive antileukemic therapy may be at lower risk of death than those who receive less-intensive antileukemic therapy, over time (HR, 0.78; 95% confidence interval, 0.69-0.89). 62,80,90,101,104,121,124,125,129,132 Very low-quality evidence suggests that the risk of death may also lower at 1 year (risk ratio, 0.93; 95% confidence interval, 0.85-1.01). 54,62,76,90,92,104,121,123,[127][128][129]132 Low-quality evidence suggests the likelihood that patients who receive intensive antileukemic therapy are 6.6 times more likely to receive an allo-HSCT than those who receive less-intensive antileukemic therapy (risk ratio, 6.65; 95% confidence interval, 4.13-10.71).…”
Section: Recommendationmentioning
confidence: 99%
“…Following the removal of duplicates, we identified 15615 potential eligible studies of which 231 proved potentially relevant based on title and abstract screening, and 25 studies (7825 patients) proved eligible on full-text review (Fig 1). From the included studies, published between published 2002 and 2020, 21 were included after the first search and informed the development of the recommendations [4,12,14,15,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], and 4 were included later [46-49]. We did not find any ongoing studies.…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies (529 patients) were prospective, multicenter RCTs conducted in France, the United Kingdom, Sweden, Italy, Germany, Spain, Australia, the United States, Poland, Belgium, Republic of Korea and Canada [15,29]. Twenty-one were retrospective observational studies (retrospective cohort study, case-control study and case series) (7296 patients) conducted in the United States [4,[30][31][32][33][34][47][48][49], France [33,[35][36][37][38][39], the Netherlands [33,40], Republic of Korea [41,42], Japan [43], China [44], Sweden [46], Italy [12,33], Austria, Germany, Portugal and Spain [33]. Two articles reported analyses of data from two trials [14] or three trials [45] in the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%